Menabung Emas Sesuai Syariah: Telaah Implementasi Prinsip Syariah di Bank BTN Syariah - Fitri Otaviyani; Dian Anugrah; Nabila Husaini; Muh Al-Furqan Nugrawahyu (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the implementation of sharia principles in the iB Gold Savings product at Bank BTN Syariah Parepare Branch Office. The focus of the study includes the implementation of the Mudharabah Mutlaqah contract, profit-sharing mechanisms, management transparency, and the role of the Sharia Supervisory Board (DPS) in ensuring operational compliance with Islamic law. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation studies. The results show that Bank BTN Syariah Parepare has implemented sharia principles optimally in all operational aspects. The Mudharabah contract is implemented with a fair profit-sharing system, namely 25% for customers and 75% for the bank, without any elements of usury, gharar, or maysir. Collaboration with PT Antam ensures the authenticity and security of customers' gold investments. In addition to providing ease of investment, the implementation of sharia principles also strengthens trust, loyalty, and the image of BTN Syariah as a financial institution based on Islamic values. The iB Gold Savings product has proven to be not only financially profitable, but also spiritually valuable because it is in line with the goals of justice and welfare in the Islamic economic system.